Long-term Outcome of Patients With Nonoperated Prosthetic Valve Infective Endocarditis: Is Relapse the Main Issue?. (9th December 2019) - Lecomte, Raphaël; Laine, Jean-Baptiste; Issa, Nahéma; Revest, Matthieu; Gaborit, Benjamin; Le Turnier, Paul; Deschanvres, Colin; Benezit, François; Asseray, Nathalie; Le Tourneau, Thierry; Pattier, Sabine; Al Habash, Ousama; et al.
Abstract: In nonoperated prosthetic valve endocarditis (PVE), long-term outcome is largely unknown. We report the follow-up of 129 nonoperated patients with PVE alive at discharge. At 1 year, the mortality rate was 24%; relapses and reinfection were rare (5% each). Enterococcal PVE was associated with a higher risk of relapse.